Maturational development as a key aspect in physiological performance and national-team selection in elite male basketball players - Arede, J.; Ferreira, A. P.; Gonzalo-Skok, O.; Leite, N. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine the discriminators as variables to select the under-16 national-team players and to examine the influence of biological age on physical/technical parameters among young basketball players. Methods: Thirty-four under-15 male basketball players performed several anthropometrical (height, wingspan, body mass, and fingers length) and physical (jumping, sprinting, throwing, flexibility, change-of-direction speed, and aerobic fitness) tests during the under-15 male national-team training camp. Maturity offset, lower-limb asymmetry index, and power outputs for jumping and sprinting were also computed. In addition, game performance was taken into consideration using game-related statistics (assists, turnovers, steals, rebounds, blocks, and points) of 5 games of during the previous regional tournament (April 2016). Cluster analysis was used to analyze the between-maturation status (prepubertal, pubertal, and postpubertal) differences in physical parameters. Results: The postpubertals showed a significantly better performance in power outputs (jumping and sprinting), throwing abilities, and blocks, whereas prepubertal performed significantly better in aerobic fitness and assists. Receiver-operating-characteristic curve confirmed maturational status (area under the curve [AUC]=0.804; P<.05) and training experience (AUC=0.789; P<.05) as the most important attributes in predicting under-16 national-team selection. Players with more than 5.5 years of training experience and less than 1.4 y to the age at peak height velocity were most likely to be selected. Conclusion: Maturational status seems to be a key variable that increases the probability of selection for the Portuguese under-16 national team.